Analisis Variasi Jarak Sumbu Poros Terhadap Tegangan Kontak Dan Tegangan Bending Pada Helical Gear Pair Berdasarkan Metode Elemen Hingga - Sopyan Ali Rohman; IDK Okariawan; Achmad Zainuri (Dinamika Teknik Mesin, 2012)
This researchs object is determining  the effect of modifying center distance to bending stress and contact stress on the helical gear pair based on the finite element method. And to know the safety factor on each center distance variation within helical gear pair.Gear being analyzed is one of the gears on Honda motor cycles branded Beat. To know the specification of gear, the helical gear geometry measurements were taken. Based on the results of measurements was carried out models of helical gear pair by AUTO CAD software. Then,  bending stress and contact stress analysis with finite element method on  ANSYS 12.1. Optimal center distance of gear pairs is determined by safety factors on the quasi statatis condition.From the research results can be concluded that the change of center distance can affect the bending stress and contact stress on gears and affect of security design. A safe center distance variation is 52.65 mm, 52,75 mm, 52,85mm and 52.95 mm.